(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The integration of digital technologies into higher education has become vital in improving teaching quality, student engagement and graduate employability. Despite supportive national policies such as Zimbabwe’s Education 5.0, technology in many universities remains underutilised for pedagogical transformation. In exploring the factors influencing the successful integration of technology into teaching and learning in higher education institutions in Zimbabwe, the study adopted the intepretivist paradigm, a qualitative research approach, as well as the case study design. Data were generated through semi-structured interviews with nine lecturers and focus group discussions with twelve undergraduate students. Data from interviews were analysed using thematic analysis, and initial coding was completed by label identification. Thematic analysis revealed that while both lecturers and students demonstrated generally positive attitudes towards digital technologies, effective integration was constrained by inadequate infrastructure, limited digital literacy, insufficient pedagogical training, high data costs, and inconsistent institutional support. Technology was largely confined to content delivery rather than interactive and student-centred learning. The study concludes that meaningful technology integration requires alignment between pedagogy, technology and content, supported by sustained professional development and institutional investment. The study also recommended that lecturers should integrate interactive and student-centred digital methods like simulations and collaborative tools rather than limiting them to content delivery. The study contributes context -specific insights into technology adoption challenges in Zimbabwean higher education.